Dimensions of quality of life of older adults in relation to selected sociodemographic variables—a prospective cohort study - Głowacka, Mariola; Sienkiewicz, Zofia; Dykowska, Grażyna; Haor, Beata (Frontiers in Public Health, 2024)
Background Based on its definition of an individual’s quality of life, the World Health Organization identified the following six basic domains of this concept: physical domain, psychological domain, level of independence, social relationships, environment and spirituality. The aim of the study was to examine these quality of life dimensions in pre-older and older adults in relation to selected sociodemographic variables. Methods The study included 2,040 adults aged 55 or older. It was conducted using a diagnostic survey by means of a questionnaire with sociodemographic questions and the EQ-5D-3L descriptive system. Results The vast majority of male and female respondents reported no problems in most EQ-5D-3L dimensions. However, the mean EQ-5D-3L index score indicated a slight difference in scores between men and women. A statistically significant difference between male and female respondents in individual dimension scores was found only for the usual activities dimension. The proportion of respondents reporting no problems decreased with age in most dimensions, except for anxiety/depression. Age was statistically significantly correlated with all individual dimension scores and the index score. The vast majority of respondents across all education levels reported no problems in most dimensions. Education was statistically significantly correlated with all individual dimension scores and the index score. Conclusion The vast majority of respondents across both sexes and all education levels reported no problems in most EQ-5D-3L dimensions. The proportion of respondents reporting no problems decreased with age in most EQ-5D-3L dimensions. Systematic research on dimensions of health-related quality of life will help design measures for healthy and successful ageing.